2015
DOI: 10.1177/0885328215588307
|View full text |Cite
|
Sign up to set email alerts
|

Development of lattice-inserted 5-Fluorouracil-hydroxyapatite nanoparticles as a chemotherapeutic delivery system

Abstract: Developing an effective vehicle for cancer treatment, hydroxyapatite nanoparticles were fabricated for drug delivery. When 5-Fluorouracil, a major chemoagent, is combined with hydroxyapatite nanocarriers by interclay insertion, the modified hydroxyapatite nanoparticles have superior lysosomal degradation profiles, which could be leveraged as controlled drug release. The decomposition of the hydroxyapatite nanocarriers facilitates the release of 5-Fluorouracil into the cytoplasm causing cell death. Hydroxyapati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…It is a pyrimidine analogue anticancer agent that functions as an antimetabolite to inhibit cell proliferation. 5-FU is effective against numerous tumors, including colorectal, breast, liver and pancreatic cancer (Tseng et al, 2015). As it is associated with a short half-life in the body (<30 min), high dose 5-FU over a long period is recommended to achieve the desired effect (Karmi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is a pyrimidine analogue anticancer agent that functions as an antimetabolite to inhibit cell proliferation. 5-FU is effective against numerous tumors, including colorectal, breast, liver and pancreatic cancer (Tseng et al, 2015). As it is associated with a short half-life in the body (<30 min), high dose 5-FU over a long period is recommended to achieve the desired effect (Karmi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(Tseng et al, 2015). 5-Fu is a cytotoxic drug, which has been used to treat cancers (Fadaeian et al, 2015) via inhibiting the synthesis of nucleic acids (Burns & Beland, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The DRX, FTIR, and Raman results showed no crystallographic or chemical modifications of neither the matrix nor the drug after the loading process that suggests the reversible interaction. The drug-matrix chemical interaction was related to the appearance or disappearance of characteristic bands after drug loading as well as relevant changes in their position, as other studies reported [15,21,80].…”
Section: Plos Onementioning
confidence: 78%
“…3from CaPs that covered the weak peaks of carboplatin in this region [50,51,56]. The presence of vibrational modes and peaks position of the drug and biomaterials indicated that the drug was attached to the CaP surface without any chemisorption process [15,80]. The minimum losses verified by load efficiency calculated (Eq 1) was expected for the loading methodology used and reflected only the losses in the process, not the adsorption capacity of calcium phosphates.…”
Section: Plos Onementioning
confidence: 94%
See 1 more Smart Citation